2010
DOI: 10.4321/s0004-06142010001000005
|View full text |Cite
|
Sign up to set email alerts
|

Cáncer de próstata como hallazgo en resección transuretral

Abstract: Resumen.-OBJETIVO: El hallazgo de adenocarcinoma prostático en piezas quirúrgicas sin diagnóstico previo de tumor se presenta en 4 a 15% de los pacientes. En algunos, existe sospecha previa, en otros, el hallazgo es "incidental". Presentamos 7 casos de cáncer de próstata detectados en 100 pacientes a quienes se les realizó resección transuretral (RTU) bipolar de próstata debido a indicaciones quirúrgicas habituales. El objetivo de este trabajo es describir las características de los pacientes en quienes se enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…The contemporary prevalence of prostate cancer incidentally found at TURP is variable, accounting for 7-17% of all diagnosed cases of prostate cancer in selected populations [2,3,4,5,6]. This observation is concordant with pathological mapping studies demonstrating the peripheral zone (PZ) as the primary focus of prostatic adenocarcinoma in a majority of cases [7,8,9].…”
Section: Introductionsupporting
confidence: 66%
“…The contemporary prevalence of prostate cancer incidentally found at TURP is variable, accounting for 7-17% of all diagnosed cases of prostate cancer in selected populations [2,3,4,5,6]. This observation is concordant with pathological mapping studies demonstrating the peripheral zone (PZ) as the primary focus of prostatic adenocarcinoma in a majority of cases [7,8,9].…”
Section: Introductionsupporting
confidence: 66%
“…They found significant decreases in the overall detection rate, 12.9 to 8%, and the amount of pT1b lesions, 10% to 5% (24). More recently, Jones et al's comparison found a decrease of incidental prostate cancer from 14.9% to 5.2% (pre versus post PSA era) in over 700 patients (25).They saw significant decreases in both pT1a and pT1b incidental prostate cancer (4.4% to 2.2% and 10.5% to 2.8%, resp.) between the pre-PSA and the PSA eras (21).…”
Section: Discussionmentioning
confidence: 96%
“…Dellavedova et al found an incidental prostate cancer detection rate of 7% when they reviewed 100 patients who underwent bipolar TURP. Six patients had Gleason grade 3 + 3 pT1a disease and one patient had Gleason grade 3 + 4 pT1b disease (25).…”
Section: Discussionmentioning
confidence: 98%
“…Entre estas se pueden mencionar:Pacientes asintomáticos con PSA elevado que pueden tener obstrucciones significativas y beneficiarse con la cirugía. 11 Valores altos de PSA se asocian a riesgo de retención urinaria. 12 La RTUP tiene baja tasa de complicaciones, que pueden reducirse aún más haciendo resecciones limitadas que eviten la resección apical y la perforación capsular.…”
Section: Discussionunclassified
“…13,14 La detección de adenocarcinoma en pacientes operados por hiperplasia oscila entre 4 y 15 % en la literatura. 11 Según la clasificación de la Unión Internacional Contra el Cáncer (UICC) del año 2002, se establece una diferencia entre T1a (hallazgo de tumor incidental en 5% o menos del tejido resecado) y T1b (hallazgo de tumor incidental en más del 5% del tejido resecado). 4 Esto se basa en el riesgo de progresión, que es sólo de 5% a los 5 años (aunque el 50% progresa entre 10 y 13 años) para T1a; en cambio, la mayoría de los casos de T1b progresan a 5 años.…”
Section: Discussionunclassified